CAMBRA Factors Correlated with Dental Caries in Children - A'yun, Quroti; Sulistyani, Herastuti; Risnawati, Dewi; Dilianti, Ika Fitri (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Recent data show that the prevalence of dental caries in children aged 10 to 14 years is almost 41.4%. Several methods for managing caries include Caries Management by Risk Assessment (CAMBRA). The CAMBRA method assists doctors in identifying causes of dental caries by identifying risk factors in each patient. Based on research, the etiology of dental caries was discovered by identifying risk factors in each participant. This study aims to identify what factors influence dental caries in children based on CAMBRA. Method: This research uses observational analysis with cross-sectional data. The respondents are students from Kadipiro I Elementary School, Bantul, Daerah Istimewa Yogyakarta, Indonesia. Purposive sampling was used to create the sample, which included 82 children between the ages of 10 and 12. The study was conducted by discovering dental caries risk factors with the CAMBRA method: 1. new cavity or lesion to dentine, 2. white spot, 3. restorations within the last three years, 4. volume of saliva, 5. plaque/ PHPM index, 6. pH saliva, and 7. frequency of sweet foods consumption. The scale of the data was nominal and analysed using the SPSS version 25.0 program, which included frequency analysis and logistic regression. Result: The results of the logistic regression analysis showed that five variables have a significant (p